2016
DOI: 10.1002/ejic.201601087
|View full text |Cite
|
Sign up to set email alerts
|

2,6‐Diisopropylanilinium Bromobismuthates

Abstract: A systematic approach to obtain bromobismuthates with various bismuth/halide ratios stabilised by 2,6-diisopropylanilinium cations [ArNH 3 ] (Ar = 2,6-diisopropylphenyl) is presented. New bromobismuthate compounds [(ArNH 3 )(BiBr 4 )] ∞ (1), [(ArNH 3 ) 3 (Bi 2 Br 9 )] ∞ (2), [(ArNH 3 ) 3 (BiBr 6 )] (3) and [(ArNH 3 ) 4 -(BiBr 6 )(Br)] (4) with Bi/Br ratios of 1:4, 1:4.5, 1:6 and 1:7 have been isolated and structurally characterised. [Bi 2 Br 9 ] ∞ is a new structural motif in halobismuthate chemistry. In all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 62 publications
3
9
0
Order By: Relevance
“…Nevertheless, the value of P s of EBB is the smallest within R 2 MX 5 -type ferroelectrics, which may be due to the relatively small dipole moment value of ethylamine (1.22 D). The value of the band gap estimated for EBB is comparable to those observed in other bromobismuthates­(III) …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, the value of P s of EBB is the smallest within R 2 MX 5 -type ferroelectrics, which may be due to the relatively small dipole moment value of ethylamine (1.22 D). The value of the band gap estimated for EBB is comparable to those observed in other bromobismuthates­(III) …”
Section: Resultssupporting
confidence: 82%
“…The value of the band gap estimated for EBB is comparable to those observed in other bromobismuthates(III). 68 Conclusions. The newly synthesized EBB belongs to a unique group of organic−inorganic hybrids based on Bi(III) characterized by the cis configuration of the [MX 5 ] ∞ 2− chains.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Additionally, a related In­(III) complex, [InCu 2 Cl 5 ­(PPh 3 ) 4 ]­·THF, has been reported that also features a distorted square-pyramidal motif . The Bi–Br distances in 3a are more uniform than the Bi–Cl distances found in 1 , ranging between 2.831 and 2.858 Å, similar to those found in compounds containing [BiBr 6 ] 3– anions (e.g., 2.755–2.981 Å in [(ArNH 3 ) 3 ­(BiBr 6 )] with Ar = 2,6-diisopropylphenyl). Once again, two fairly unequal M–X bond length of 2.715 and 2.956 Å are observed together with a nearly trigonal-planar coordination environment at the silver atom, indicating a 3 + 1 coordination sphere, as seen in 1 , although the difference between a longer and shorter M–X bond is less pronounced here and rather close to the range observed for silver bromide phosphine complexes with typical Ag–Br distances between 2.60 and 2.93 Å …”
Section: Resultssupporting
confidence: 61%
“…(2) (Liu et al, 2006), [Bi 6 Cl 26 ] 8À (Leblanc et al, 2010), [Bi 7 I 24 ] 3À (Hamdeh et al, 2016) and [Bi 8 Cl 28 ] 4À (Adonin et al, 2014), where single-and double-halo bridges are mainly found and, in some cases, halo bridges span three Bi III centres. There are 84 polymeric examples with single-halo-bridged [Bi n X 5n ] 2nÀ anions, 60 with cis-double-halo-bridged [Bi n X 4n ] nÀ anions and 24 with more complex anionic systems; examples being [Bi 6n I 20n ] 2nÀ (Heine, 2015), [Bi 6n I 22n ] 4nÀ (Heine, 2015) and [Bi 2n Br 9n ] 3nÀ (Pandey et al, 2017). There are no examples of double-halo-bridged [Bi n X 4n ] nÀ anionic chains where the terminal halo ligands are trans-disposed.…”
Section: Introductionmentioning
confidence: 99%